KEBERLAKUAN HUKUM ADAT DAN UNDANG-UNDANG POKOK AGRARIA DALAM PENENTUAN HAK ATAS TANAH TIMBUL - Bambang Eko Turisno (Masalah-Masalah Hukum, 2011)
Regarding the status of sandbar, for local communities arising from the village communal land controlled by the village is, on the other side the land is state land arise. Local laws that are not written during this proved not only cheaper but also much more to protect local interests. Granting land rights arise, the interests protected include individual interests, public interest and importance to protect and recognize the values upheld in the society, protection of natural resources which is a social interest.